Human age estimation using bio-inspired features - Guodong Guo; Guowang Mu; Yun Fu; Huang, Thomas S (2009 IEEE Conference on Computer Vision and Pattern Recognition, 2009)
We investigate the biologically inspired features (BIF) for human age estimation from faces. As in previous bio-inspired models, a pyramid of Gabor filters are used at all positions of the input image for the S 1 units. But unlike previous models, we find that the pre-learned prototypes for the S 2 layer and then progressing to C 2 cannot work well for age estimation. We also propose to use Gabor filters with smaller sizes and suggest to determine the number of bands and orientations in a problem-specific manner, rather than using a predefined number. More importantly, we propose a new operator "STD" to encode the aging subtlety on faces. Evaluated on the large database YGA with 8,000 face images and the public available FG-NET database, our approach achieves significant improvements in age estimation accuracy over the state-of-the-art methods. By applying our system to some Internet face images, we show the robustness of our method and the potential of cross-race age estimation, which has not been explored by any studies before.